EQUITABLE VERTEX COLORING OF SUDHA GRAPHS S(n,m) - SUDHA, S.; RAJA*, G. M. (International Journal of Mathematical Archive, 2018)
Sudha et al. [7] found equitable vertex coloring of Sudha graph  and found its chromatic number is either 3 or 4 according to  or . In this paper, we have extended our discussion of equitable vertex coloring to the Sudha graph  for  and its chromatic number lies between 2 and 4.